2009
DOI: 10.1080/00050060802680598
|View full text |Cite
|
Sign up to set email alerts
|

Publication trends in individual DSM personality disorders: 1971–2015

Abstract: Growth in personality disorder research has been documented by previous authors up to 1995. The aim of the present study was to extend this by examining publications rates for individual DSM personality disorders over the period 1971-2005, and making projections to 2015 based on these data. It was found that personality disorder research has grown in absolute terms, and as a proportion of overall psychopathology research. Research output is dominated by borderline personality disorder, with strong publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…For example, Blashfield and Intoccia (2000) suggested that only the literatures concerning antisocial, borderline, and schizotypal are "alive and well" (p. 473). Boschen and Warner (2009) reached a similar conclusion in their more recent meta-analysis. However, the meta-analysis by Blashfield and Intoccia was limited by the fact that their search terms were confined to studies in which the full title of the disorder (i.e., dependent personality disorder) had to be included in the title of the study, effectively missing a considerable amount of empirical research concerning (for instance) dependent personality traits, dependency, or even dependent personality (Widiger, 2011a).…”
Section: Discussionsupporting
confidence: 74%
“…For example, Blashfield and Intoccia (2000) suggested that only the literatures concerning antisocial, borderline, and schizotypal are "alive and well" (p. 473). Boschen and Warner (2009) reached a similar conclusion in their more recent meta-analysis. However, the meta-analysis by Blashfield and Intoccia was limited by the fact that their search terms were confined to studies in which the full title of the disorder (i.e., dependent personality disorder) had to be included in the title of the study, effectively missing a considerable amount of empirical research concerning (for instance) dependent personality traits, dependency, or even dependent personality (Widiger, 2011a).…”
Section: Discussionsupporting
confidence: 74%
“…Clearly, BPD is both a contested and stigmatized psychiatric diagnosis, particularly when used with younger people (Koehne, Hamilton, Sands, & Humphreys, 2013), and so BPD generates more research and associated debate than all the other personality disorders (Boschen & Warner, 2009). The BPD diagnosis is frequently critiqued as a construction which pathologizes any deviation from societal norms (Shaw & Proctor, 2005), and this is particularly apparent with female patients (Wirth‐Cauchon, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The construct problems and the fact that until now, NPD has only rarely been studied (Boschen & Warner, 2009;Alarcon & Sarabia, 2012;Morey & Stagner, 2012) call the clinical benefits of the description of the disorder into question (Krueger, 2010), and they were crucial to the initial lack of intention to include the diagnosis of NPD in DSM-5 (American Psychiatric Association, 2013). When this decision was made public, this led to great controversy (Shedler et al, 2010;Pilkonis et al, 2011), which demonstrated that NPD has many supporters who emphasize its clinical relevance (e.g., Pincus & Lukowitsky, 2010).…”
Section: Criticism Of Npdmentioning
confidence: 99%